SYNTHESIS AND CHARACTERIZATION OF TRIAQUATRISULFISOKSAZOL COBALT(II)SULPHATE.nHYDRATE COMPLEX - Sentot Budi Rahardjo; Abu Masykur; Melin Puspitaningrum (Indonesian Journal of Chemistry, 2006)
Complex of cobalt(II) with sulfisoxazole (slfs) has been synthesized in 1 : 4 mole ratio of metal to ligands in methanol, the complex formula is [Co(slfs)3(H2O)3]SO4.nH2O. The electric conductivity of the complex in methanol correspond to 1:1 electrolyte. The thermal analysis indicates that complex contain some hydrates. Magnetic Susceptibility measurements show that the complex is paramagnetic with µeff = 4,60(9) BM. Infra red spectra indicates that the primary N-H group coordinated to the center ion, it is signed by a shift of primary N-H group absorption. UV-Vis spectrum appears one peak at λ= 515,5 nm (19.342 cm-1) due to transition peak of 4T1g (F) → 4T2g (P) (ν3) overlay to transition peak of 4T1g(F) → 4A2g(F) (ν2). The value of 10 Dq (Δo) that corresponds to transition 4T1g → 4T2g (n1) is 95,29 kJ.mol-1. Cyclic voltammograms have revealed quasi reversible. The complex probably is octahedral.